Relationship between serum iohexol clearance, serum SDMA concentration, and serum creatinine concentration in non‐azotemic dogs - Myles McKenna; Ludovic Pelligand; Jonathan Elliott; Daniel Cotter; Rosanne Jepson (Journal of Veterinary Internal Medicine, 2020)
Abstract Background Serum creatinine and symmetric dimethylarginine (SDMA) are used as surrogate markers of glomerular filtration rate (GFR) in clinical practice. Data pertaining to the correlations between GFR, SDMA, and serum creatinine in client‐owned dogs are limited. Objectives To describe the relationship between GFR, SDMA, and serum creatinine in a population of client‐owned dogs, and to compare clinical utility of SDMA to GFR estimation for detecting pre‐azotemic chronic kidney disease. Animals Medical records of 119 dogs that had GFR estimation performed via serum iohexol clearance between 2012 and 2017. Methods Prospective study using archived samples. GFR, SDMA, and serum creatinine results were reviewed and submitting practices contacted for outcome data. All dogs included in the study population were non‐azotemic. Correlations between GFR, SDMA, and serum creatinine were determined by regression analysis. Sensitivity, specificity, and positive and negative likelihood ratios of different cutoffs for SDMA and serum creatinine for detecting decreased GFR were calculated, using a 95% confidence interval. Results Serum creatinine and SDMA were moderately correlated with GFR (R2 = 0.52 and 0.27, respectively, P < .0001) and with each other (R2 = 0.33, P < .0001). SDMA >14 μg/dL was sensitive (90%) but nonspecific (50%) for detecting a ≥40% decrease in GFR. Optimal SDMA concentration cutoff for detecting a ≥40% GFR decrease was >18 μg/dL (sensitivity 90%, specificity 83%). Conclusions and Clinical Importance In non‐azotemic dogs being screened for decreased renal function, using a cutoff of >18 μg/dL rather than >14 μg/dL increases the specificity of SDMA, without compromising sensitivity.